Gran - Hunt, Roderick; Brychta, Alex (Oxford Oxford University press, 2012)
Gran comes to visit and surprises everyone with her adventurous spirit. Through simple text and engaging illustrations, young readers will enjoy following Gran's escapades as she takes the children on an unexpected adventure, showing that she is not an ordinary grandmother. This delightful story helps to build early reading skills and encourages a love for reading.
"Gran" is a part of the Oxford Reading Tree (ORT) series, specifically designed for early readers. The book features engaging illustrations and simple text to help young children develop their reading skills. It is an ideal resource for promoting literacy, encouraging children to read independently, and building their confidence with familiar and relatable stories. Location: 1A
Keywords: Oxford Text-book